A Legal Protection Model For Handling Human Trafficking in West Kalimantan Border - Azizurrahman, Syarif hasyim; Ismawati, Sri; Lolita, Lolita; Elyta, Elyta (Faculty of Law, Universitas Pekalongan, 2024)
Although it is a highly serious human crime, people trafficking still occurs, particularly in West Kalimantan's border region. West Kalimantan's border region has seen a variety of attempts to reduce human trafficking, yet the practice persists still. There is a need for a solution or model that can lessen instances of human trafficking in the West Kalimantan border region, carried out so that the parties involved are unaware of it.This study aims to develop an appropriate model for legal protection to deal with human trafficking at the border West Kalimantan. Methods of the Research, The research will be conducted at the Polres in the Sajingan and Biawak border regions, as stated in the research title. The Sajingan Besar sector's Resort Police and Border Communities are two sources of crime prevention strategies based on legal requirements, The study's findings serve as a model for public protection from human trafficking activities from the perspective of the role of law enforcement officials, the police in the border regions of Sajingan and Biawak, in particular, to combat the crime of trafficking in persons, conduct investigations, and look into cases of human trafficking that happened in the border regions of Sambas Regency, particularly Sajin. The criminal law (penal) is used by the authorities as a model of legal protection to stop human trafficking. However, there is still human trafficking that takes place. Because there are still several barriers to sentencing that do not take into account the elements of a crime. The unlawful behavior in place does not yet constitute the TIP factor. Using criminal law policies and cultural norms to carry out criminal crimes like human trafficking, protecting the public, and implementing coordination with illegal law enforcement policies all help to enhance efforts to combat corruption